UMP prioritises welfare and safety of students - Siti Nur Azwin, Zulkapri (2020)
The government’s decision to extend the Movement Control Order (MCO) from 31 March until 14 April is considered the best step taken to fight the spread of the Covid-19 outbreak across the country.